Determination of cutter-head geometry for the face-milling of hypoid gears. Issue 9 (October 2016) - Wasif, Muhammad; Chen, Zezhong; Hasan, Syed
Abstract Special-purpose multi-axis CNC machines are used for the face-milling of hypoid gears. These machines are equipped with specially design cutter-head, consisting of inside and outside blades, to machine the convex and concave sides of the gear teeth. In this research, CAD model of a face-milling cutter-head is developed, in which side cutting edges of inside and outside blades of the cutter system are built on the rake face. Since the side cutting edges are not on the axial plane of the cutter, the sweep surface formed by the cutting edges are hyperboloids, rather than the cylindrical surfaces as assumed in the other researches. Due to the hyperboloid sweep surfaces of the cutter, the gear teeth formed by the face-milling have not only curvature along the length of the teeth but also have curvature along the flank-wise direction. It leads towards the result that the blade angles are not equal to the flank angles of the gear teeth at the mean point. Therefore, a CAD-based cutter geometry determination model is built, to calculate the geometry parameter of the cutter-head, such as blade angles and the average cutter radius, for the given parameters of the gear teeth at the mean point.